Effect of Suruhan Leaves (Peperomia pellucida L. Kunth) Extract on Triglyceride Blood Level in Diabetic Rats - Hafita Dinda Maryana; Nainggolan, Hotlina; Nadia Rusyda Hanifa (Universitas Airlangga, 2024)
Background: Diabetes Mellitus causes complications, such as hypertriglyceridemia. Indonesia has biological wealth diversity that can be exploited in alternative medicine. One of which is Suruhan plants. Flavonoid contents in the plant extract can normalize blood triglyceride levels. Objective: This study aims to determine the effect of the Suruhan extract (Peperomia pellucida L. Kunth) on blood triglyceride levels in alloxan-induced diabetic white rats. Methods: The induction process used alloxan at a dose of 150mg/kgbw intraperitoneally to 12 rats. The rats were divided into 5 research groups, namely normal rats, diabetic rats, and diabetic rats were given various doses of extract. The treatment was carried out for 14 days. Blood samples for triglyceride examination were taken at the end of the study. Results: blood triglyceride levels were obtained in the normal group (127.67 mg/dl); and diabetic control group (395.67mg/dl); the dose group was 20mg/kg BW (216mg/dl); the dose group was 40 mg/kg BW (159.33 mg/dl) and the dose group was 80 mg/kg BW (143.33 mg/dl) in the statistical test with one way ANOVA (p <0.05) obtained significance with a value of p = 0.000. Conclusions: There is an influence of plant extracts (Peperomia pellucida [L.] Kunth) administration on the blood reduction of triglyceride levels in diabetic white rats induced by alloxan.